Cholesterol-lowering Potential and Exopolysaccharide Biosynthesis of Lactobacillus spp. isolated from Human Milk - Uyen, Pham Thi Thu; An, Nguyen Hoai; Hai, Pham The; Ha, Bui Thi Viet (VNU Journal of Science: Natural Sciences and Technology, 2021)
Recent research generated information that human milk is not only a valuable source of nutrition, but it also provides a complex microbial community, containing especially Lactobacillus species - the major components of a great number of commercial probiotics. New findings on potential applications of Lactobacillus species revealed that these bacteria have abilities to produce anti-microbial exopolysaccharides (EPS) and to reduce cholesterol in culture broth. In this study, we successfully isolated and screened for Lactobacillus bacteria from human milk samples, and finally obtained four strains, including L. plantarum BM7.13, L. plantarum BM29.7,  L. acidophilus BM10.8 and L. rhamnosus BM30.4. Researching the probiotic activities of these strains showed that all strains were tolerant to the low pH (3.0) and 0.3% bile salts. Characterization of the probiotic properties indicated that all selected Lactobacillus isolates had ESP (125-326 mg/L) and exhibited strong antimicrobial activities against pathogenic microbes, such as Escherichia coli, Staphylococcus aureus, Shigella flexneri and Salmonella typhimurium . Our results also indicated that all strains displayed cholesterol assimilation capabilities in culture broth with the maximum figure recorded for L. plantarum BM7.13.